2008
DOI: 10.1166/jnn.2008.n05
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Doped Zinc Oxide Nanowires

Abstract: Zinc oxide (ZnO) nanowires were grown via thermal transport and subsequently doped with different concentrations of Tm, Yb, and Eu using ion implantation and post annealing. High ion fluences lead to morphology changes due to sputtering; however, freestanding nanowires become less damaged compared to those attached to substrates. No other phases like rare earth (RE) oxides were detected, no amorphization occurs in any sample, and homogeneous doping with the desired concentrations was achieved. Photoluminescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…We show this comparison because it has been reported that, during RE ion implantation into ZnO, the dopant atoms are distributed homogeneously. 28 We find that DE is sufficiently large in favor of FM coupling in Gd-doped ZnO nanowires in the neutral state. A significant DE (as high as 21 meV) is obtained for the nearest neighbor Gd atoms in the neutral state.…”
Section: Resultsmentioning
confidence: 71%
“…We show this comparison because it has been reported that, during RE ion implantation into ZnO, the dopant atoms are distributed homogeneously. 28 We find that DE is sufficiently large in favor of FM coupling in Gd-doped ZnO nanowires in the neutral state. A significant DE (as high as 21 meV) is obtained for the nearest neighbor Gd atoms in the neutral state.…”
Section: Resultsmentioning
confidence: 71%
“…A fully relaxed device with low initial conductivity of ≈ 0, 5 nA increases its conductivity to 6 nA in distinct steps during ≈ 350 s of exposure. Terbium was used for this implantation to show that the PIC effect is not at all ion specific and because rare earths show interesting optical effects in ZnO [21].…”
mentioning
confidence: 99%
“…To grow p ‐type ZnO, the acceptor concentration has to be higher than the unintentional donor concentration. Different authors have reported the effect of doping with V‐group elements such as As, P, N, and effect of doping also with Tm, Yb, and Eu using ion implantation and post annealing was reported in the literature . Recently, also Sb has been proposed as acceptor doping …”
Section: Preparation Techniques and Growth Mechanismsmentioning
confidence: 99%